Karakteristik Dan Preferensi Wisatawan Nusantara Yang Berkunjung Ke Kebun Raya Bogor - Putra, Elang Adichandra Hedyana; Sudiarta, I Nyoman; Dewi, Luh Gede Leli Kusuma (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i01.p19, 2024)
To effectively manage a tourist destination with a sustainable concept, an in-depth understanding of the characteristics and preferences of tourists visiting the site is crucial. This study aims to investigate the characteristics of domestic tourists visiting Bogor Botanical Gardens. Data collection methods include observation, questionnaires, documentation, and literature review, with quantitative data analysis employed for the research. The characteristics of tourists at Bogor Botanical Gardens are predominantly female, aged between 18-25 years, mostly students, originating from DKI Jakarta. They are motivated to visit the gardens for recreational and relaxation purposes with family or relatives, typically making one visit with a duration of 3-5 hours and staying in hotels for 1-6 days. They tend to organize their travel activities independently, utilizing social media as their primary source of travel information, with an income ranging from Rp 0 - Rp 5,000,000 and average expenditure below Rp 500,000 when visiting Bogor Botanical Gardens. Picnicking is the preferred attraction at the gardens, while parks, green areas, and conservation spaces are the favorite facilities for tourists. Regarding infrastructure, roads and pathways are favored options. In terms of transportation, cars are the preferred mode of transport when visiting Bogor Botanical Gardens, while ease of obtaining information at the gardens is the favorite choice for tourists in terms of hospitality. Bogor Botanical Gardens is encouraged to utilize the research findings as a reference for the development of sustainable tourism at the site. Keywords: Tourist characteristics, Tourist preferences, Bogor Botanical Gardens, Domestic tourists, Sustainable tourism